(untitled) (Biodiversitas Journal of Biological Diversity, 2007)
Some actinomycetes which were isolated from Bukit Bangkirai fire forest in East Kalimantan have been identified. Those isoates were also characterized for its cellulolitic and phosphate solubilizing ability. Identification was based on Miyadoh (1997) and Holt (1994) methods. Actinomycetes could be identified by microscopic observation on spores, chain spore, hypha, aerial hypha and its pigmentation. The cellulolitic ability was observed by clear zone ratio in CMC medium and phosphate solubilizing activity by same approach in Pikovskaya medium. From 91 Bukit Bangkiraiâ€™s actinomycetes isolates which had been deposited in LIPI Microbial Collection (LIPIMC) were identified as 7 genera (Streptomyces, Nocardia, Microbiospora, Micromonospora, Microtetraspora, Streptosporangium and Actinoplanes). 57,14 % phosphate solubilizing actinomycetes and 38,46 % cellulolitic actinomycetes were detected with clear zone ratio average of 1,48 and 1,59 respectively. Â© 2007 Jurusan Biologi FMIPA UNS Surakarta Key words: Actinomycetes, spore, chain spore, aereal hypha, phosphate solubilizing, cellulase